Asymptotic symmetries of Maxwell theory in arbitrary dimensions at spatial infinity - Erfan Esmaeili (Journal of High Energy Physics, 2019)
Abstract The asymptotic symmetry analysis of Maxwell theory at spatial infinity of Minkowski space with d ≥ 3 is performed. We revisit the action principle in de Sitter slicing and make it well-defined by an asymptotic gauge fixing. In consequence, the conserved charges are inferred directly by manipulating surface terms of the action. Remarkably, the antipodal condition on de Sitter space is imposed by demanding regularity of field strength at light cone for d ≥ 4. We also show how this condition reproduces and generalizes the parity conditions for inertial observers introduced in 3+1 formulations. The expression of the charge for two limiting cases is discussed: null infinity and inertial Minkowski observers. For the separately-treated 3d theory, the boundary conditions and charges are compared to null infinity results in the literature. We also compute the conserved charges for background isometries for d > 3.